The immune protection induced by a serine protease from the Trichinella spiralis adult against Trichinella spiralis infection in pigs. - Daoxiu Xu; Xue Bai; Jing Xu; Xuelin Wang; Zijian Dong; Wenjie Shi; Fengyan Xu; Yanfeng Li; Mingyuan Liu; Xiaolei Liu (Public Library of Science (PLoS), 2021)
Trichinellosis is a major foodborne parasitosis caused by Trichinella spiralis. In the present study, a serine protease gene from an adult T. spiralis (Ts-Adsp) cDNA library was cloned, expressed in Escherichia coli and purified by Ni-affinity chromatography. Previous studies of our laboratory have found that mice vaccinated with recombinant Ts-Adsp protein (rTs-Adsp) exhibited partial protection against T. spiralis infection. In this study, the protective effect of rTs-Adsp against T. spiralis infection in pigs was further explored. The cell-mediated and humoral immune responses induced by rTs-Adsp were measured, including the dynamic trends of specific antibody levels (IgG, IgG1, IgG2a and IgM), as well as the levels of cytokines (IFN-γ, IL-2, IL-4, and IL-10) in the serum. Moreover, the changes in T lymphocytes, B lymphocytes, and neutrophils were measured to evaluate cellular immune responses in pigs vaccinated with rTs-Adsp. The results indicated that a Th1-Th2 mixed immune response with Th1 predominant was induced by rTs-Adsp after vaccination. Flow cytometric analysis showed that the proportions of CD4+ T cells, B cells, and neutrophils in the immunized groups were significantly increased. Furthermore, pigs vaccinated with rTs-Adsp exhibited a 50.9% reduction in the muscle larvae burden, compare with pigs from the PBS group five weeks after challenged. Our results suggested that rTs-Adsp elicited partial protection and it could be a potential target molecule for preventing and controlling Trichinella transmission from pigs to human.